Liquid Crystalline Polymers Volume 1-Structure and Chemistry - Thakur, Vijay Kumar; Kessler, Michael R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book introduces anisotropic innovations in liquid crystalline polymers as well as new nanocomposite materials and testing techniques. The authors detail the newest discoveries of material properties, material types and phases, and material characterization.  This interdisciplinary work creates valuable links that strengthen the approach to the evolving field of liquid crystalline polymers/materials.
Introduction -- Basic concepts -- Development -- Material properties -- Synthesis Techniques -- Chemistry.
Keywords: Nanotechnology; Polymers; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Materials -- Analysis; Nanotechnology; Polymers; Engineering Thermodynamics, Heat and Mass Transfer; Characterization and Analytical Technique